Solar energy digitalization at high latitudes: A model chain combining solar irradiation models, a LiDAR scanner, and high-detail 3D building model - Manni, Mattia; Nocente, Alessandro; Kong, Gefei; Skeie, Kristian; Fan, Hongchao; Lobaccaro, Gabriele (Frontiers in Energy Research, 2022)
Solar mapping can contribute to exploiting more efficiently the solar energy potential in cities. Solar maps and 3D solar cadasters consist of visualization tools of solar irradiation analysis on urban surfaces (i.e., orography, roofs, and facades). Recent advancements in solar decomposition and transposition modelling and Light Detection And Ranging (LiDAR) scanning enable high level of detail 3D solar cadasters, in which the façade domain is considered besides the roof. In this study, a model chain to estimate solar irradiation impinging on surfaces with different orientations at high latitudes is developed and validated against experimental data. The case study is the Zero Emission Building Laboratory in Trondheim (Norway). The main stages of the workflow concern (i) data acquisition, (ii) geometry detection, (iii) solar radiation modelling, (iv) data quality check, and (v) experimental validation. Data is recorded from seven pyranometers installed on the facades (4), roof (2), and pergola (1), and used to validate the Radiance-based numerical model, over the period between June 21st and September 21st. This study investigates to which extent high-resolution data sources for both solar radiation and geometry are suitable to estimate global tilted irradiation, at high latitudes. In general, the Radiance-based model is found to overestimate the solar irradiation. Nonetheless, the hourly solar irradiation modelled for the two pyranometers installed on the roof are experimentally validated in accordance with the ASHRAE Guideline 14. When monthly outcomes are considered for validation, also the east and the south pyranometers are validated. The achieved results build the ground for the further development of the 3D solar cadaster of Trondheim.